Whole-body MRI in the assessment of disease activity in juvenile dermatomyositis. Issue 6 (1st May 2013) - Malattia, Clara; Damasio, Maria Beatrice; Madeo, Annalisa; Pistorio, Angela; Providenti, Anna; Pederzoli, Silvia; Viola, Stefania; Buoncompagni, Antonella; Mattiuz, Chiara; Beltramo, Agnese; Consolaro, Alessandro; Ravelli, Angelo; et al.
Abstract : Objective: To compare whole-body MRI (WB-MRI) with clinical examination in the assessment of disease activity in juvenile dermatomyositis (JDM). Methods: WB-MR images were obtained from 41 JDM patients and 41 controls using a 1.5 T MRI scanner and short τ inversion recovery sequences. 18 patients had follow-up WB-MRI. Muscle, subcutaneous tissue and myofascial signal abnormalities were scored in 36 muscular groups and on proximal and distal extremities. WB-MRI and clinical assessments were performed concurrently and results compared. Validation procedures included analysis of feasibility, reliability, construct validity, discriminative ability and responsiveness. Results: WB-MRI revealed distal legs (26/41 patients) and forearm (19/41 patients) muscle inflammation undetected during clinical examination and allowed an accurate assessment of subcutaneous (23/41 patients) and myofascial involvement (13/41 patients). 27 patients showed a patchy distribution of muscle inflammation while in seven the abnormal hyperintense areas tended to be homogeneously distributed. The inter-reader agreement for muscular, subcutaneous and myofascial WB-MRI scores was excellent. Correlations between WB-MRI muscle score and disease activity measures were excellent (Manual Muscle Test: rs=−0.84, Childhood Myositis Assessment Scale: rs=−0.81). WB-MRI score was higher in JDM active patients when compared with the control group (pB <0.0001) and the inactive patients (pB =0.004), and showed an excellent responsiveness (standardised response mean=1.65). Follow-up WB-MRI showed resolution of inflammation in nine patients whereas clinical criteria for remission were satisfied in five. Conclusions: WB-MRI provides additional information to clinical evaluation and represents a promising tool to estimate total inflammatory burden, tailor treatment and monitor its efficacy.